Ethanolic Extract of Secang (Caesalpinia sappan L.) Wood Performs as Chemosensitizing Agent Through Apoptotic Induction on Breast Cancer MCF-7 Cells - Khamsita, Rahmi; Hermawan, Adam; Putri, Dyaningtyas Dewi Pamungkas; Meiyanto, Edy (Indonesian Research Gateway, 2012)
Resistance to chemotherapy is believed to cause treatment failure of the patient cancer. Secang (Caesalpinia sappan L.) has been proven to possess anticancer activity on some cancer cell lines. The aimed of this study to develop ethanolic extract of secang wood (EES) as chemosensitizing agent through apoptotic induction on breast cancer MCF-7 cells. Extraction of secang was done by using maceration with 70 % ethanol. Single and combinatorial treatment of EES and doxorubicin on MCF-7 breast cancer cells were analyzed by using MTT assay to determine the IC50 value and combination index (CI) to evaluate the combinatorial effect. Apoptosis was analyzed with flowcytometry (annexin V). EES showed a dose-dependent cytotoxicity (IC50 value of 37 µg/ml), while combinatorial treatment showed that 7 concentrations was found to be synergist with doxorubicin on MCF-7 cells. Combinatorial treatment also triggered apoptotic instead of single treatment. Based on this result, we conclude that ethanolic extract of secang wood is potential as chemosensitizing agent in breast cancer.Keyword: Caesalpinia sappan L, MCF-7 cells, doxorubicin, apoptosis.